2016
DOI: 10.1038/srep36908
|View full text |Cite
|
Sign up to set email alerts
|

Potential costs of heterospecific sexual interactions in golden orbweb spiders (Nephila spp.)

Abstract: Though not uncommon in other animals, heterospecific mating is rarely reported in arachnids. We investigated sexual interactions among four closely related and syntopical African golden orbweb spiders, Nephila inaurata, N. fenestrata, N. komaci, and N. senegalensis. In two South African localities, female webs were often inhabited by heterospecific males that sometimes outnumbered conspecifics. Species association of males with females was random in nature. In subsequent laboratory choice experiments, N. inaur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Given the functions of genes involved, these changes might be costly to the female, affecting not only fertilization, but also could alter hybrid performance (if fertilization succeeds) as well as subsequent nutritional and egg-laying decisions by the female. These types of changes have been detected in a few species [69][70][71], but their transcriptional basis and evolutionary rates have remained unknown. Our results indicate that transcriptional perturbation following heterospecific mating extends beyond the female reproductive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Given the functions of genes involved, these changes might be costly to the female, affecting not only fertilization, but also could alter hybrid performance (if fertilization succeeds) as well as subsequent nutritional and egg-laying decisions by the female. These types of changes have been detected in a few species [69][70][71], but their transcriptional basis and evolutionary rates have remained unknown. Our results indicate that transcriptional perturbation following heterospecific mating extends beyond the female reproductive tract.…”
Section: Discussionmentioning
confidence: 99%
“…A study of four African Trichonephila species (121) found that 20-60% of webs harbored the wrong species of males, who guarded the wrong females and competed among themselves and against heterospecific males. Heterospecific mating occurred but resulted in no offspring (121). Because Trichonephila komaci has significantly smaller (weaker) males than the other species studied, and is both rare and range restricted, the authors hypothesized that T. komaci experiences reproductive interference.…”
Section: Reproductive Interferencementioning
confidence: 99%
“…However, in the case of heterospecific courtship, males are unlikely to gain any benefit from courting a heterospecific, but they pay the same cost; one male in our study was attacked several times by a heterospecific female who eventually captured and ate him. There is growing evidence in spiders that courtship displays incur both energetic and viability costs for males, as well as increased risk of predation [4, 8, 16, 28, 50–53]. However, we argue that what makes spiders a particularly intriguing system to examine misdirected courtship is the risk of predation from females, a cost that is only rarely examined in this context (see review in [9]).…”
Section: Discussionmentioning
confidence: 94%
“…However, many animals (e.g., ground-hoppers, moths, flies, ticks, lizards, fish) invest time and energy courting heterospecifics with which they never mate or are unable to produce viable offspring (reviewed in [9]), or even attempt mating with inanimate objects (e.g., [10]). In addition to simply wasting energy that could be invested in other activities, such misdirected courtship (or ‘reproductive interference’) can also reduce or prevent viable mating opportunities for both sexes (e.g., [1116]). Given such costs, we might expect selection to favor mechanisms that prevent or reduce misdirected courtship.…”
Section: Introductionmentioning
confidence: 99%